A REVIEW OF PIEZOELECTRIC PVDF FILM BY ELECTROSPINNING AND ITS APPLICATIONS - Kalimuldina, Gulnur; Turdakyn, Nursultan; Abay, Ingkar; Medeubayev, Alisher; Nurpeissova, Arailym; Adair, Desmond; Bakenov, Zhumabay (MDPI, 2020)
With the increase of interest in the application of piezoelectric polyvinylidene fluoride (PVDF) in nanogenerators (NGs), sensors, and microdevices, the most efficient and suitable methods of their synthesis are being pursued. Electrospinning is an effective method to prepare higher content β-phase PVDF nanofiber films without additional high voltage poling or mechanical stretching, and thus, it is considered an economically viable and relatively simple method. This work discusses the parameters affecting the preparation of the desired phase of the PVDF film with a higher electrical output. The design and selection of optimum preparation conditions such as solution concentration, solvents, the molecular weight of PVDF, and others lead to electrical properties and performance enhancement in the NG, sensor, and other applications. Additionally, the effect of the nanoparticle additives that showed efficient improvements in the PVDF films was discussed as well. For instance, additives of BaTiO3, carbon nanotubes, graphene, nanoclays, and others are summarized to show their contributions to the higher piezo response in the electrospun PVDF. The recently reported applications of electrospun PVDF films are also analyzed in this review paper.
Keywords: piezoelectricity; PVDF; electrospinning; nanogenerator; sensors; self-charging; PENG; PVDF nanofibers; Research Subject Categories::TECHNOLOGY